Diversity of Hymenoptera parasitoid in organic and conventional arabica coffee plantations in Aceh Tengah District, Aceh Province, Indonesia. Issue 1 (February 2021) - Saifullah,; Husni, H; Jauharlina, J; Hamdi, S
Abstract: This research is a descriptive exploratory study. The purpose of this study was to determine the diversity of parasitoids in coffee plantations that are managed organically and conventionally. Based on statistical analysis shows that the composition and diversity of the Hymenoptera parasitoid in Arabica coffee plantations in Aceh Tengah District is influenced by cultivation techniques (organic and conventional). Both the number of families and species of Hymenoptera parasitoid found in organic coffee plantations were higher than those found in conventional ones. In organic coffee plantations, 8 families and 15 species were found, while in conventional plantations there were only 4 families and 10 species. The parasitoid species diversity index value (H') in organic coffee plantations was better than conventional coffee plantations, while the evenness index value (E) on organic and conventional coffee plantations was relatively more likely (not statistically different) and to be classified as good categories. This indicates that there are several families of the Hymenoptera parasitoid that dominate both in organic and in conventional coffee plantations. The low diversity of the Hymenoptera parasitoid in conventional coffee plantations is thought to be a result of the continued application of synthetic pesticides, thus affecting the extinction of various parasitoid species.